TEOLOGI PENCIPTAAN DAN TANGGUNG JAWAB LINGKUNGAN: Pendekatan Kristen terhadap Krisis Ekologis - Esty Kurniawaty; Andi, La'bi Ratte Langi', Arni Tanggulungan, Yunitsar Trimulia Sari (ADISAM PUBLISHER, 2024)
This study will examine the relationship between the theology of creation in the Christian tradition and environmental responsibility amidst the global ecological crisis. Ecological crises, such as climate change, pollution, and biodiversity loss, have become serious challenges that require ethical and theological reflection. The Christian approach to creation emphasizes the idea that the universe is God's good work, and humans are entrusted as stewards of the earth. In this context, the study explores the concept of creation in the Bible, particularly in the book of Genesis, as well as the teachings of Christian theologians regarding the relationship between humans and nature. This research seeks to understand how human responsibility for the environment can be enhanced through theological understanding of creation, sin, and salvation. Using literature review and theological analysis methods, this study shows that Christian theology has great potential to contribute to environmental conservation efforts by emphasizing humanity's moral obligation to preserve the integrity of creation. The implication is that churches and Christian communities are expected to play an active role in advocacy and tangible actions to address the ecological crisis globally.